"A storehouse of prisoners": Rio de Janeiro's Correction House (Casa de Correção) and the birth of the penitentiary in Brazil, 1830–1906. Issue 2 (3rd April 2017) - Jean, Martine
ABSTRACT: This article chronicles the construction of Rio de Janeiro's Correction House, the Casa de Correção between 1830 and 1906. I examine why more than 60 years after its inauguration in 1850 the penitentiary was perceived as a failed experiment in liberal penal reform by Brazilian statesmen. In the second quarter of the nineteenth century, Brazilian liberals from the Society for the Defense of Freedom and National Independence – Sociedade Defensora da Liberdade e Independência Nacional – turned to the Atlantic's marketplace of ideas to shape their views on confinement which they held as pivotal for establishing Brazil's place in the world of civilized nations. They drew their understandings on the penitentiary primarily from an 1826 commission's report from the Society for the Improvement of Prison Discipline and the Reformation of Juvenile Offenders, and from American penology, mainly Auburn's "congregate" and Pennsylvania's "separate" system. Local ideas about order and the racial hierarchies of the slave economy shaped Brazilian adaptation of liberal penal reforms. My analysis of the origins of the Casa de Correção emphasizes the significance of the penitentiary as a hybrid penal institution that unevenly incorporated liberal penal reforms developed in north-Atlantic settings with locally grown understandings of the function of confinement to contain rather than rehabilitate the lower classes.